2021
DOI: 10.1002/ctm2.635
|View full text |Cite
|
Sign up to set email alerts
|

GRAMD4 inhibits tumour metastasis by recruiting the E3 ligase ITCH to target TAK1 for degradation in hepatocellular carcinoma

Abstract: Background Aberrant TAK1 (transforming growth factor β‐activated kinase 1) activity is known to be involved in a variety of malignancies, but the regulatory mechanisms of TAK1 remain poorly understood. GRAMD4 (glucosyltransferase Rab‐like GTPase activator and myotubularin domain containing 4) is a newly discovered p53‐independent proapoptotic protein with an unclear role in HCC (hepatocellular carcinoma). Results In this research, we found that GRAMD4 expression was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Mechanistically, GRAMD4 inhibited HCC migration, invasion, and metastasis by promoting TAK1 degradation. 25 Recent research has demonstrated the clinical relevance of TAK1 in promoting HCC and sorafenib resistance. Combining TAK1 inhibitors with sorafenib inhibited the growth of sorafenib-resistant HCCLM3 xenografts in mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, GRAMD4 inhibited HCC migration, invasion, and metastasis by promoting TAK1 degradation. 25 Recent research has demonstrated the clinical relevance of TAK1 in promoting HCC and sorafenib resistance. Combining TAK1 inhibitors with sorafenib inhibited the growth of sorafenib-resistant HCCLM3 xenografts in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…TAK1 deletions or losses can be detected in various types of human cancers and are positively associated with tumour progression and poor patient survival. [16] , [17] , [18] , [19] , [20] Elevated TAK1 expression and activity have also been detected in several human cancers, [21] , [22] , [23] , [24] including hepatocellular carcinoma (HCC), 25 , 26 indicating a dual role of TAK1 in regulating tumour initiation, progression, and metastasis. Mice with hepatocyte-specific deletions of TAK1 developed spontaneous liver fibrosis and hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the direct targets that mediated NUF2's biological actions in malignancies, particularly in CCA, were not well understood. In this study, we performed RNAseq and mass spectrometry analysis and identified TFR1 and MAPK which served as cancer promoting factors to promote the development of various tumors [38][39][40][41][42]. Therefore, we first explored the role of NUF2/ TFR1/MAPK axis in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the p38 pathway, ITCH acts inhibiting it, from one hand by targeting TXNIP for ubiquitin-dependent proteasome degradation, and from the other hand by catalyzing the K48-linked ubiquitylation and degradation of TAB1, a known activator of p38 [75,76]. In relation to the JNK pathway, ITCH has been described to regulate MKK4 ubiquitylation and subsequent degradation, thus decreasing JNK activation [77]. The HECT E3 ligases WWP1 and SMURF1 have also been related with the regulation of the three conventional MAPK signaling pathways ERK1/2, p38 and JNK.…”
Section: The Role Of Hect Ubiquitin Ligases In the Regulation Of Mapk...mentioning
confidence: 99%